Kadsura induta A. C. Smith (Schisandraceae Blume) a new record for the flora of Vietnam - Thanh, Bui Van; Cuong, Nguyen The; Ban, Ninh Khac (Academia Journal of Biology, 2012)
The genus Kadsura Juss. (Schisandraceae Blume) comprises 16 species, distributed in the Asia region. Five species of Kadsura previously described and illustrated from flora of Vietnam are K. angustifolia A. C. Smith, K. coccinea A. C. Smith, K. heteroclita Craib., K. longipedunculata Fin & Gagnep. and K. oblongifolia Merr. The K. induta A. C. Smith was known from China only (Guangxi and Yunnan). Recently, we collected a species   Kadsura  induta A. C. Smith in Sapa district, Lao Cai province. The specimens of voucher are keeping in the Hanoi herbarium at the Institute of Ecology and Biological Resource, Hanoi (HN). K. induta A. C. Smith is recorded first time in Vietnam. The key to five species,  recorded from Vietnam and K. induta is redescribed and illustrated.